STRENGTHENING BAZNAS AS THE SOCIETY’S TRUSTED ZAKAT AGENCY TO INCREASE THE WELFARE OF UMMAH - Al-Fatih, Sholahuddin (Fakultas Syariah, 2020)
Zakat potential in Indonesia reaches IDR 252 trillion per year. With the amount of 202 million Muslims, this can alleviate poverty in Indonesia. However, zakat has not been optimized by the government. This is indicated by the low tax revenue which is around USD 86 Million per month or IDR 2.8 Trillion per year. Low zakat collection is partly caused by the lack of trust to zakat management institutions (called LPZ), LPZ’s professionalism, and zakat direct distribution by muzakki to mustahik. In addition, people worry that their funds will be corrupted. It is because corruption is closely related to government’s image; shown by abundant cases of corruption involving well-known figures. This article discusses the role of zakat in alleviating poverty and reinforcing Baznas as public’s reliable Amil Zakat Institution (BAZ). The result indicated that the professionalism of services and management of BAZ and LAZ can be created by improving their performance to gain community trust. One effort of empowering BAZ as public trust is through the internal and external reinforcement. Baznas internal reinforcement can be done by tightening Human Resource recruitment and assessment by national and international accreditation agencies. Meanwhile, external reinforcement is done by creating innovation and program rebranding.Potensi zakat di Indonesia cukup tinggi dan mencapai Rp. 252 triliun per tahun. Dengan 202 juta populasi Muslim, potensi zakat dapat membantu mengurangi kemiskinan di Indonesia. Namun, zakat belum dapat dioptimalkan oleh pemerintah. Ini ditunjukkan oleh pendapatan pajak yang rendah sekitar USD 86 juta per bulan atau IDR 2,8 triliun per tahun. Pengumpulan zakat yang rendah sebagian disebabkan oleh tingkat kepercayaan publik terhadap lembaga pengelolaan zakat (LPZ), profesionalisme LPZ dan distribusi zakat langsung oleh muzakki ke mustahik. Selain itu, masyarakat khawatir dana zakat yang disetorkan akan dikorupsi. Hal ini terjadi karena korupsi sangat berkaitan dengan imej pemerintah; terbukti dengan banyaknya kasus korupsi yang melibatkan tokoh-tokoh penting di pemerintahan. Artikel ini membahas peran zakat dalam pengentasan kemiskinan dan penguatan Baznas sebagai Badan Amil Zakat (BAZ) kepercayaan publik. Hasil menunjukkan bahwa profesionalisme layanan serta manajemen BAZ dan LAZ dapat diciptakan dengan meningkatkan kinerja mereka untuk mendapatkan kepercayaan dari masyarakat. Salah satu upaya memberdayakan BAZ sebagai kepercayaan publik adalah melalui penguatan internal dan eksternal. Penguatan internal Baznas dapat dilakukan dengan memperketat rekrutmen SDM dan penilaian oleh lembaga akreditasi nasional dan internasional. Sementara penguatan eksternal dibuat dengan inovasi dan rebranding program.